Platelet Volume Indices as Non - Invasive Physiological Marker of Liver Fibrosis in Chronic Hepatitis C Patients - Yar Mohammad Nizamani; Aamir Hussain; Ahmed Hussain Suhag (JLUMHS, 2017)
BACKGROUND: Mean platelet volume (MPV), platelet distribution width (PDW) and P-LCR (platelet large cell ratio) are known platelet volume indices (PVI). Currently, the platelet volume indices (PVI) have emerged to determine its value as biomarker of liver fibrosis. OBJECTIVES: The present study determined the Platelet volume indices (PVI) as non invasive physiological marker of liver fibrosis in chronic hepatitis C patients. STUDY DESIGN: Case control study STUDY SETTINGS: Department of Gastroenterology, ISRA University Hospital and Asian Institute of Medical Sciences (AIMS) Hyderabad from May- December 2014. SUBJECTS AND METHODS: A sample of 64 patients; 32 controls and 32 chronic hepatitis C cases were studied. Subjects were selected by non-probability (purposive) sampling as per inclusion and exclusion criteria. Roche Hitachi Hematolyzer was used for platelet count and platelet volume indices. Liver fibrosis was determined from liver biopsies by METAVIR Score. Data was analysed on Statistix 10.0 (USA) at 95% confidence interval (P<0.05). RESULTS: The PVI (MPV, PDW and P-LCR) and platelet count were raised in cases compared to controls (p<0.05). PVI showed major differences for METAVIR SCORE F0 -F4 of liver fibrosis (p<0.05). MPV, PDW and P-LCR showed positive correlation (r= 0.93, r= 0.80 and r= 0.75) with METAVIR (p <0.0001) respectively. CONCLUSION: The Platelet volume indices may be used as non-invasive physiological markers for liver fibrosis in chronic hepatitis C patients instead of invasive technique of liver biopsy.